Comparative analysis of sagittal condylar guidance by protrusive interocclusal records with panoramic and lateral cephalogram radiographs in dentulous population: A clinico-radiographic study - Girish Galagali; Sufiyan M Kalekhan; Prakash Nidawani; Jagadeesh Naik; Sidhartha Behera (Wolters Kluwer Medknow Publications, 2016)
Aim : To evaluate and compare the correlation between sagittal condylar guidance obtained by protrusive interocclusal records mounted on semi-adjustable articulator with panoramic and Lateral cephalogram radiograph tracings in dentulous population. Materials and Methods: One-hundred twenty dentulous subjects between age group of 20-40 years, free of signs and symptoms of any temporomandibular diseases were selected. The sagittal condylar guidance was determined by protrusive interocclusal records and transferred to a semi-adjustable articulator through a face bow. The condylar guidance angles obtained were tabulated. The sagittal outline of the articular eminence and glenoid fossa were traced on panoramic and lateral cephalogram radiographs. The sagittal condylar path inclination was constructed. This was related to the Frankfurt's horizontal plane on radiograph to determine the radiographic angle of sagittal condylar guidance. The comparison of protrusive interocclusal records was done with the angles obtained by panoramic and lateral cephalogram radiograph tracings. Results: The mean difference between the condylar guidance values obtained using panoramic and lateral cephalogram radiographs was 0.13° and 0.67° on right side and 1.0° and 1.54° on left side with the radiographic values being higher. A Significant positive correlation was observed with P values 0.001 and 0.005 in left and right respectively. Conclusion: This study highlighted on the correlation between protrusive interocclusal records and the lateral cephalogram radiograph tracings which were more positively related than the panoramic radiograph. The values of lateral cephalogram radiograph tracings are closer as separate radiographs for left and right side were taken, causing the amount and quality of image distortion less. Lateral cephalogram radiograph may be taken as an important tool to rely on for recording the Sagittal condylar guidance angle.